KONTRIBUSI FUNGSI KELUARGA TERHADAP PENCEGAHAN PENULARAN HIV AIDS PADA KALANGAN REMAJA DI DESA SAMPANG SEMPOR KABUPATEN KEBUMEN - -, Marsito; Saraswati, Rina (Jurnal Ilmiah Kesehatan Keperawatan, 2016)
The number of HIV AIDS cases reached seven cases in Sempor subdistrict in 2014. That was a rather high number in each subdistrict in Kebumen district. In Sampang village, the number of adolescence around 1186 people (15,5%) in 2010. This existence showed that it was very high in Sampang village, in addition to create the risk of disease occurrence due to the deviation of less healthy behaviors that can lead to the occurrence of free sex. This study aimed to correlate the contribution of family function towards the prevention of HIV AIDS transmission among adolescents in Sampang village. This study used descriptive correlation study design with cross sectional approach to the variables consisted of independent variables, such as age, sex, the contribution of family affective function, family social function, family economic function, family reproductive function, and family health care function. Dependent variable consisted of the prevention of HIV AIDS transmission among adolescents in Sampang village, Sempor. The sample number was 150 adolescents aged 13 to 21 years. This study used univariat and bivariate analysis with chi square test. Results showed that sex was not correlated with the prevention of HIV AIDS transmission (p = 0.120); there was relationship between age and the prevention of HIV AIDS transmission (p = 0.000); there was correlation between the contribution of family affective function with the prevention of HIV AIDS transmission (p = 0.000); the contribution of family social function was correlated with the prevention of HIV AIDS transmission (p = 0.000); the contribution of family economic function was correlated with the prevention of HIV AIDS transmission (p = 0.000); the contribution of family reproductive function was correlated with the prevention of HIV AIDS transmission (p = 0.000); the contribution of family health care function was correlated with the prevention of HIV AIDS transmission (p = 0.000). Thus, the family functions must be optimized in role to educate teens to avoid the deviation of less healthy behaviors. How the role of community nurses can optimize the task of the family functions through coaching to the vulnerable families of behavior deviation among adolescents. Â  Keywords: family function, and the prevention of HIV-AIDS transmission of adolescents